2018
DOI: 10.1007/s00203-018-1524-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into the activity and mechanism of cyanide hydratase enzyme associated with cyanide biodegradation by Serratia marcescens

Abstract: The present study provides molecular insights into the activity and mechanism of cyanide hydratase enzyme associated with degradation of cyanide compounds, using Serratia marcescens RL2b as a model organism. Resting cells harvested after 20 h achieved complete degradation of 12 mmol l cyanide in approximately 10 h. High-performance liquid chromatography analysis of reaction samples revealed formation of formamide as the only end product, which confirmed the presence of cyanide hydratase activity in S. marcesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The presence of a CynH was also suspected in the bacterium Serratia marcescens [26] after a reaction product corresponding to formamide was found in HPLC. The putative CynH sequence had a shorter amino acid chain than typical CynHs (326 residues).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a CynH was also suspected in the bacterium Serratia marcescens [26] after a reaction product corresponding to formamide was found in HPLC. The putative CynH sequence had a shorter amino acid chain than typical CynHs (326 residues).…”
Section: Introductionmentioning
confidence: 99%
“…To date, several reports have described the ability of microorganisms to grow on cyanide compounds; bacterial communities such as Pseudomonas, capable of degrading cyanide 10 mg L -1 [10] and two isolates of this genus, immobilized on activated charcoal, degrading concentrations up to 340 mg L -1 [10,11] . Arthrobacter sp., Zoogloearamigera, Acidovorax sp., Achromobacter sp., Janthinobacterium sp., Klebsiella sp., Bacillus pumillus, Burkhoderia cepacia, Alcaligenes sp., Serratia marcescen and Rhodococcus sp., among others, have been reported as cyanide degrading organisms [6,[12][13][14][15][16][17][18][19]. Besides bacteria, species of the archaeal genus Methanosarcina (under anaerobic conditions), some fungi like Fusarium solani and Trichoderma polysporum at pH 4 [20] and some algae like Scenedesmus obliquus [21] have been reported to degrade cyanide.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that cyanide degradation by Serratia marcescens species forms formamide at the end which evidences the cyanide hydratase enzymatic pathway (KUSHWAHA et al, 2018).…”
Section: % 56%mentioning
confidence: 91%